The effects of omega-3 plus vitamin E and zinc plus vitamin C supplementation on cardiovascular risk markers in postmenopausal women with type 2 diabetes. (August 2014) - Mahmoodi, Mohammad Reza; Kimiagar, Masoud; Mehrabi, Yadollah
Background: We investigate the effects of omega-3 plus vitamin E and vitamin C plus zinc supplementations on cardiovascular risk markers in postmenopausal women with type 2 diabetes. Methods: In this double-blind placebo-controlled clinical trial, 75 postmenopausal women with type 2 diabetes were randomly assigned to one of three groups to take, daily, for 12 weeks: (1) 1.8 g omega-3 fatty acids plus 400 mg vitamin E; (2) 5 mg zinc plus 300 mg vitamin C; or (3) a placebo. Results: Although the cardiovascular risk markers variations decreased at the end of intervention, we did not find any significant differences in cardiovascular risk markers between therapeutic groups and the control group. Results of repeated measures analysis of variance (ANOVA) of markers showed that total cholesterol, low-density lipoprotein (LDL) cholesterol, Apo A1 and Apo B100 in two time periods were significant ( p = 0.001). The level of total and LDL cholesterol decreased significantly ( p = 0.05) in patients diagnosed with diabetes equal or less than 7 years in the group receiving omega-3 plus vitamin E. However, decreased LDL cholesterol ( p = 0.003) and increased high-density lipoprotein (HDL) cholesterol ( p = 0.03) were predominant in patients who had been diagnosed with diabetes equal or less than 7 years in the group receiving zinc plus vitamin C. Conclusion: The effectiveness of nutraceutical supplementation was varied on biochemical biomarkers based on the kind of supplement or supplement pharmacogenomics, duration of diabetes affected and other pathophysiologic status in studied groups.